Clarification of Watershed Recharge in Cisadane River Basin through Ground Test - Dina P.A Hidayat; Sri Legowo W. D; Mohammad Farid (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2022)
KARDAS is an area used to protect groundwater from its usage as a water source. Meanwhile, the recharge zone is normally determined in Indonesia through the Regulation of the Ministry of Public Works and Housing (Permen PUPR) Number 10/2015 with the focus on certain physical parameters such as soil texture, land use/land cover, annual rainfall, and slope provided with relative potency values from 1 which represents very low to 5 which is very high. This system was used to review four parameters in a small grid unit of 1 km2 each in the Cisadane River Basin with a 1,545.47 km2 area divided into 1,710 units and the most dominant grid placed at the middle part while the rest are at the edge of the basin. This research focused on the clarification methods to determine the potential recharge variables for this river basin in order to serve as a reference for the potential recharge zone in Indonesia. The KARDAS map obtained showed a very high potential with a score of 17-20 covering 183 km2 (10.45%), high potential with a score of 13-16 involving 943 km2 (56.96%), medium potential with 584 km2 (32.59%), and 0 small potential. Moreover, KARDAS desk study results were clarified using the field or ground test to ensure accuracy and this involved using 14 units as samples to represent the five potentials through temporary quantitative cumulative scores. The desk study or secondary data results were found to be only 50% accurate with a limited point survey but the application of qualitative perception showed that only 1 point does not match with the medium and high potentials this indicates the accuracy was 93% which is categorized to be good.